Study about of On-scene Patient Care of The Emergency Medical Responder in the Southern Region of Thailand - Sungkamuneejinda, Kritsana; Chantra, Rungnapa; Jantatame, Pongthorn; Chuchan, Yindee; Weerakhachon, Phakkhanat; Suppawongsanond, Wandee (Princess of Naradhiwas University Journal, 2019)
This qualitative research aims to study about of on-scene patient care of the emergency medical responder in the southern region of Thailand. The sampled provinces were selected using purposive sampling representing the mountainous, sea-side, urban, and the conflicted area. The provinces included Surat Thani, Nakhon Si Thammarat, Trang, and Yala. Data were collected from four focus groups of 10 registered emergency medical responder in each province as well as the in-depth interviews of 20 participants including the Head of the Provincial Notification Center, two Head of the Rescue Center and two Head of the Emergency room of the provincial hospital for each province. The data was analyzed using content analysis. This qualitative research aims to study about of on-scene patient care of the emergency medical responder in the southern region of Thailand. The sampled provinces were selected using purposive sampling representing the mountainous, sea-side, urban, and the conflicted area. The provinces included Surat Thani, Nakhon Si Thammarat, Trang, and Yala. Data were collected from four focus groups of 10 registered emergency medical responder in each province as well as the in-depth interviews of 20 participants including the Head of the Provincial Notification Center, two Head of the Rescue Center and two Head of the Emergency room of the provincial hospital for each province. The data was analyzed using content analysis. The result indicated the four factors impacting the on-scene patient care of the Emergency Medical Responder in the Southern region of Thailand including 1) Knowledge of emergency medical responder, particularly on the practical use; 2) Capability, quality, and adequacy of equipment/tools for patient care; 3) Pressured environment on the scene and; 4) Online media that positively and negatively affects patient care. Therefore, relevant agencies should seek out measures to further improve their capability, readiness, and regulations that would facilitate the on-scene operation of the emergency medical responder.